2012
DOI: 10.1128/cvi.05248-11
|View full text |Cite
|
Sign up to set email alerts
|

Blastomyces dermatitidis Antigen Detection by Quantitative Enzyme Immunoassay

Abstract: The second-generation MVista Blastomyces antigen enzyme immunoassay was not quantitative; therefore, specimens obtained previously were tested in the same assay as new specimens to assess the change in antigen levels. Furthermore, the sensitivity in serum had not been fully evaluated. The purpose of this study was to evaluate a quantitative Blastomyces antigen assay and detection of antigen in serum. Calibrators containing known concentrations of Blastomyces galactomannan were used to quantify antigen in urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 13 publications
3
86
1
Order By: Relevance
“…Similar to prior reports in people and dogs,7, 8, 9, 10 we found urine Blastomyces antigen to be highly sensitive for the diagnosis of blastomycosis (100% sensitivity in this population). The sensitivity for serum antigen test was also quite high (about 90%), which is similar to previous reports (87%) 8.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to prior reports in people and dogs,7, 8, 9, 10 we found urine Blastomyces antigen to be highly sensitive for the diagnosis of blastomycosis (100% sensitivity in this population). The sensitivity for serum antigen test was also quite high (about 90%), which is similar to previous reports (87%) 8.…”
Section: Discussionsupporting
confidence: 90%
“…In the absence of organism identification, diagnosis has been accomplished historically through a combination of clinical signs, radiographic findings, and serum antibodies 2, 4, 5, 6. Recently an antigen test has been developed, which detects a cell wall galactomannan, and has been found to have a high degree of both sensitivity and specificity for the diagnosis of blastomycosis in dogs and humans 7, 8, 9, 10. Although both urine and serum can be assayed to evaluate the presence of Blastomyces antigen, urine antigen measurement appears to have an increased sensitivity relative to serum antigen for the diagnosis of blastomycosis in dogs 8…”
mentioning
confidence: 99%
“…In another human subject study, antigenuria was detected in approximately 90% of patients with proven blastomycosis. Specificity was 99% in healthy subjects or patients with nonfungal infections, but cross-reactions occurred in approximately 96% of patients with histoplasmosis [16]. An earlier study on antigen detection in dogs with blastomycosis revealed a sensitivity value of 94% in urine specimens and a value of 87% in serum specimens [7].…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this present study was to compare different antibody-antigen combinations for the detection of antigen in urine specimens from dogs with diagnosed blastomycosis. Several recent studies have focused on antigen detection in blastomycosis in humans and dogs [7,15,16]. In one study, detectable antigenuria was achieved in approximately 85% of the subjects with newly diagnosed blastomycosis, but B. dermatitidis antigen was also detected in 15 patients with histoplasmosis [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation